Evaluation of clopidogrel response in healthy cats using a novel viscoelastic test and thromboelastography - Rosati, Tommaso; Jandrey, Karl E.; Stern, Joshua A.; Nguyen, Nghi; Li, Ronald H. L. (Frontiers in Veterinary Science, 2024)
Cats with cardiomyopathy face an increased risk of arterial thromboembolism (ATE). Although clopidogrel is frequently utilized to mitigate this risk, feline responses to this therapy exhibit variability. This study evaluated 2 viscoelastic devices, thromboelastography (TEG) and Viscoelastic Coagulation Monitor (VCM), for monitoring clopidogrel in cats in comparison to light transmission aggregometry (LTA).28 healthy cats received clopidogrel for 7 days. Blood was collected at baseline and after treatment for analysis by TEG, VCM, and LTA.On LTA, maximum amplitude, slope, and area under the curve (AUC) significantly decreased after treatment (p<0.0001). On VCM, maximum clot firmness (MCF) significantly increased after treatment (p=0.002). On TEG, R-time significantly prolonged (p=0.024), while K and alpha angle significantly changed (p=0.0002 and p=0.0014, respectively). There was a moderate negative correlation between TEG R-time and LTA AUC (r=-0.39, p=0.042). Eight cats were identified as non-responders to clopidogrel. Of the 8 non-responders, 6 (75%) had shortened R time after treatment. VCM appeared to be less discriminatory in identifying non-responders.LTA remained the gold standard of monitoring clopidogrel treatment in cats. Unexpected changes on VCM and TEG were likely related to high interindividual and assay variability and increased